O papel da avaliação olfativa no diagnóstico da doença de alzheimer em idosos sulbrasileiros : um estudo exploratório - Wehrmann, Letícia (2019)
The incidence of Alzheimer's disease (AD), the most common type of dementia reported, has been growing every year and is accompanying an aging population. Usually when the diagnosis of the disease occurs there has already been an extensive and irreversible brain damage. The medications available on the market only help to slow the progression of the disease, but are far from being curative. Several studies published in the last years report hyposmia, or decreased olfactory ability, as one of the first detectable symptoms of the disease, and may appear about 15 to 20 years before cognitive symptoms. Hyposmia for AD is more abrupt and more severe than that observed during healthy aging, and may occur in about 85% to 90% of the diagnosed patients. Therefore, the development of practical, sensitive and effective methodologies that contribute to a more accurate and early diagnosis are necessary. Objectives: The main objective of the research is to evaluate the application of the Sniffin Sticks® extended kit (global gold standard) for elderly patients with or without memory impairment in a population from southern Brazil. Methods: This is a cross-sectional study. 10 patients with AD, 11 patients with mild cognitive impairment (MCI) and 10 controls without neurological diseases were sequentially selected. Patients above 60 years, who fit the inclusion criterias were evaluated. These patients were submitted to functional clinical assessment scales, neuropsychological tests, and to the Sniffin’ Sticks® extended olfactory evaluation (olfactory threshold, discrimination and identification). Results: results on the TDI score (sum of threshold, discrimination and identification evaluations) demonstrated significant differences between the AD’s group and the other groups (CO and MCI); CO: 28,6 (25,0-33,9); CCL: 25,5 (22,5-27,3), DA (6,8-17,5), p= 0,001. Results are maintained even after age adjustments. There is positive correlation between TDI score and cognitive evaluations: MoCA 0,647 (p<0,001), Mini Mental 0,591 (p<0,001), RAVLT total 0,640 (p<0,001), RAVLT delayed recall 0,638 (p<0,001). Conclusion: it was possible to correlate healthy controls with normosmia, mild cognitive impairment (MCI) patients with hiposmia and AD patients with anosmia (p<0,001), demonstrating that olfactive impairment may be a useful tool for early diagnose of MCI and AD.